PELATIHAN PEMBUATAN BROSUR DAN PAMFLET MENGGUNAKAN CANVA SEBAGAI PENDUKUNG KEGIATAN USAHA PADA KOPERASI WANITA ATSIRI CITAYAM BOGOR - Bakhri, Syamsul; Hanif, Aswar; Hendrian, Yayan; Martanto, Markus Lilik (Jurnal Pengabdian Masyarakat Nasional, 2024)
The use of information technology has great potential to improve performance and add value for small and medium enterprises (MSMEs), so that they can compete more effectively. Marketing is a key aspect in the success of MSMEs, which helps in reaching target audiences, building brand awareness, generating leads and sales, and building relationships with customers. Brochures and pamphlets are important marketing tools for MSMEs, used to introduce their products or services, as well as explain the unique proposition they offer. However, many MSMEs face difficulties in creating effective and attractive brochures and pamphlets. Canva is a graphic design platform that can help MSMEs create professional-looking brochures and pamphlets without requiring design experience. Therefore, structured training is needed to help them utilize information technology more effectively. Bina Sarana Informatika University will carry out community service activities by providing training in making brochures and pamphlets using Canva to the Atsiri Citayam Bogor Women's Cooperative. This training aims to provide knowledge and skills to cooperative members in using this graphic design platform. In this way, it is hoped that the participants can create more brochures and pamphlets so that their effectiveness in helping their activities is even higher